Enhancing Students’ Receptive Vocabulary Knowledge through Word Mapping Strategy - Ridwan, Revi Nur (Ma'soem University, 2025)
This study aims to enhance junior high school students' receptive understanding by utilizing word mapping strategies. This research employs a quantitative method with a quasi-experimental design. The study focuses on second-grade students in public junior high schools in Bandung, totaling 382 students spread across 10 classes. After randomizing the classes, class B was selected as the experimental class, and class A was the control class. The data collection techniques used in this study were a pretest and a posttest. The data analysis technique used in this study was a statistical analysis of Chi-Square to compare pre-test and posttest values. The results of the hypothesis test showed that the value of Tcount was 4 > 2.64 (Ttable), then H0 was rejected and Ha was accepted, meaning there was a significant difference in receptive vocabulary mastery between students who used conventional learning techniques and word mapping strategies. Thus, teachers could use word mapping strategies to improve vocabulary learning for institutions, teachers, students, and future researchers effectively.